Training on The Use of Telang Flowers as Food Coloring for Women Who Sell Traditional Foods in Kotagede - Herni Setyawati; Muhammad Lukman Baihaqi Alfakihuddin; Nurhidayati; Heriani; Wuri Ratna Hidayani; Rini Oktavera; Lina Maulidiana; Prety Diawati; Siti Nurhayati; Resy Nirawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This community engagement project aimed to empower ten traditional food vendors in Kotagede, Yogyakarta, by training them to utilize butterfly pea (Clitoria ternatea) flowers as natural food coloring. Employing a participatory approach, the training covered health risks of synthetic dyes, the benefits and cultivation of butterfly pea plants, natural dye extraction techniques, and basic product branding. Data were collected through pre- and post-tests, observation, and semi-structured interviews. Results showed a significant increase in participants’ knowledge and practical skills, with post-test scores rising across all indicators. Most participants successfully applied the extract in traditional dishes and reported improved consumer interest due to the natural and visually appealing color. Some began cultivating the plants and branding their products with natural labels. Despite minor challenges regarding shelf life and packaging, the training effectively promoted innovation, health awareness, and entrepreneurship among women food vendors. This program highlights the potential of locally sourced natural ingredients in supporting sustainable, health-conscious food businesses.